2007
DOI: 10.1002/hep.21747
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted magnetic resonance imaging for the assessment of fibrosis in chronic hepatitis C

Abstract: Liver biopsy is the gold standard for assessing fibrosis but has several limitations. We evaluated a noninvasive method, so-called diffusion-weighted magnetic resonance imaging (DWMRI), which measures the apparent diffusion coefficient (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
185
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(200 citation statements)
references
References 35 publications
11
185
2
2
Order By: Relevance
“…DW-MRI using R2-ADC values also failed to predict postoperative hepatic insufficiency (P=1.000) and the performance of DW-MRI in the prediction of advanced liver fibrosis (F3-4) and cirrhosis (F4) was disappointing (AUROC=0.648, P=.313 and AUROC=0.491, P=.938, respectively), despite our use of a 3-T MRI system which could have potentially provided better sensitivity to diffusion effects [14]. Furthermore, The R2-ADC values for each fibrosis stage did not show a tendency to increase or decrease.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…DW-MRI using R2-ADC values also failed to predict postoperative hepatic insufficiency (P=1.000) and the performance of DW-MRI in the prediction of advanced liver fibrosis (F3-4) and cirrhosis (F4) was disappointing (AUROC=0.648, P=.313 and AUROC=0.491, P=.938, respectively), despite our use of a 3-T MRI system which could have potentially provided better sensitivity to diffusion effects [14]. Furthermore, The R2-ADC values for each fibrosis stage did not show a tendency to increase or decrease.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, Lewin et al reported that the performance of DW-MRI was comparable to that of other noninvasive tests for assessing liver fibrosis in patients with chronic hepatitis C (CHC) (AUROC=0.79 for F2-4 and 0.92 for F3-4) and concluded that DW-MRI could be used as an adjunctive imaging modality to assess liver fibrosis in patients for whom liver MRI is performed [14]. In their study, the performance of LSM was similar or slightly superior to that of DW-MRI (AUROC=0.87 for F2-4 and 0.92 for F3-4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diffusing water spins within a voxel experience phase dispersion, causing signal attenuation that is dependent on the (12,17,18,47,50), and for liver tumor treatment response (6,11,14,20,(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%